Efecto de la metodología de Polya en el desarrollo de la resolución de problemas matemáticos en los estudiantes de grado cuarto (2018)
This research proposal covered the effect of the implementation of the methodology, based on the Pólya method, with which it was sought to facilitate the learning of the resolution of mathematical problems of the students of the fourth grade of Basic Education of the Departmental Educational Institution “Arcesio Cáliz Amador” (IEDACA) of El Banco Magdalena. Analysis categories were analyzed, such as the understanding, configuration, execution of a plan, vision and retrospective, of the methodological procedure of Pólya, by means of a previous test, the way of proceeding of the students was diagnosed in the solution of mathematical problems in situations and analyzed. Additive and multiplicative. In this sense, the research is based on a quantitative paradigm, with a work design of 45 students of the Institution. The results obtained through the posttest method allowed us to recognize that the demographic studies and the process developed by them, the process of the mistakes they made in carrying out an operation and the plan until the review of their results; additionally it was identified that the averages of the percentages of achievement in the test of solving the mathematical problems of multiplicative additive type for the control and experimental group, 58.18% and 91.38%.